An Empirical Assessment on Perceived Service Quality of Organized Retail Outlets - Nellai Kumar, jothi; P Marishkumar, Dr. (International Journal of Engineering and Technology, 2018)
This Project research studies the scenarios, complications, difficulties and promotional benefits of constructing an all-encompassing, ways to transaction with SQM in retailing sector. The research is identified the Â of SQM and tools of quality. Sachin borgave (2015). This article identifies the association between the satisfaction, and loyalty in the organised retail outlets. Â Â (Marishkumar P. , 2014; Gronroos 1984) is used. The sample size was 400 consumers of organised retail outlets placed in south tamilnadu. The dimensions were characterized into Assurance, Empathy, Reliability, Responsiveness, Tangibility. The factor analysis with SPSS was used to test the hypotheses. Â Â Â